2004
DOI: 10.1016/j.taap.2003.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Chronic health effects in people exposed to arsenic via the drinking water: dose?response relationships in review

Abstract: Chronic arsenic (As) poisoning has become a world wide public health issue.Most human As exposure occurs from consumption of drinking water containing high amounts of inorganic As (iAs). In this paper, epidemiological studies conducted on the dose-response relationships between iAs exposure via the drinking water and related adverse health effects are reviewed. Before the review, the methods for evaluation of the individual As exposure are summarized and classified into two types, i.e. the methods depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
272
0
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(281 citation statements)
references
References 27 publications
(28 reference statements)
0
272
0
9
Order By: Relevance
“…Individuals with documented As-BD are considered for more aggressive screening for long-term complications, especially the development of malignancies in the lung and urinary bladder [77][78][79][80]. It was indicated that As-BD started within 10 years, invasive skin cancer after 20-30 years [81], and pulmonary cancer after 30 years following the suspected arsenic exposure [76]. Therefore, the characteristic pathological and clinical features of As-BD may provide evidences of arsenic-induced cellular responses in the early stages of chemical carcinogenesis.…”
Section: Arsenic and Skin Cancermentioning
confidence: 99%
“…Individuals with documented As-BD are considered for more aggressive screening for long-term complications, especially the development of malignancies in the lung and urinary bladder [77][78][79][80]. It was indicated that As-BD started within 10 years, invasive skin cancer after 20-30 years [81], and pulmonary cancer after 30 years following the suspected arsenic exposure [76]. Therefore, the characteristic pathological and clinical features of As-BD may provide evidences of arsenic-induced cellular responses in the early stages of chemical carcinogenesis.…”
Section: Arsenic and Skin Cancermentioning
confidence: 99%
“…The Journal of Immunology, 2008, 180: 6010 -6017. 3 is an environmental toxicant to which millions of humans are exposed worldwide, mainly through contaminated drinking water (1). Chronic exposure to this metalloid is associated with skin lesions (2), vascular inflammatory diseases (3), and cancers (4).…”
Section: Inorganic Arsenic Activates Reduced Nadph Oxidase In Human Pmentioning
confidence: 99%
“…Arsenic is widely distributed in nature and released into the environment through natural sources, industrial processes and agriculture usage (Singh et al 2010;Chio et al 2009;Chatterjee et al 1995;Mandal et al 1996;Duker et al 2005;Tapio and Grosche 2006). Continued ingestion of arsenic for a long period leads to chronic arsenic poisoning; acute poisoning typically include vomiting, oesophageal and abdominal pain, diarrhoea, skin lesions, cancer of the skin, lungs, urinary bladder, and kidney, as well as other skin changes such as pigmentation changes and thickening (hyperkeratosis), black foot disease (Rahman et al 2005;Atkins et al 2007;Yoshida et al 2004;Chaudhuri et al 2008;Pandey et al 2002;Jack et al 2003;Duker et al 2005;Tseng et al 2005). Because of high impact on human health even at low concentrations several regulating agencies set their maximum contamination level of arsenic in drinking water values e.g., World Health Organization as 0.01 mg/l, French as 0.015 mg/l, United State Environmental Protection Agency as 0.01 mg/l, Vietnam and Mexico as 0.05 mg/l, European Union as 0.01 mg/l, Australia as 0.007 mg/l, Germany as 0.01 mg/l, Bangladesh and India as 0.05 mg/l (Anawar et al 2003;Choong et al 2007;Maji et al 2008;Zhu et al 2009;Barakat and Sahiner 2008;Mohapatra et al 2008).…”
Section: Introductionmentioning
confidence: 99%